2013
DOI: 10.1097/01.sa.0000426600.55897.f7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Distribution of Morphine and Metabolites in Cerebrospinal Fluid and Plasma With Chronic Intrathecal Morphine Infusion in Humans

Abstract: Background-Despite widespread use of chronic intrathecal (IT) infusions of morphine, there is little systematic human work evaluating the steady-state morphine concentrations or cerebrospinal (CSF) chemistry after long-term IT morphine delivery. We sought to address these issues in patients receiving chronic IT morphine infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Many animal studies have shown a rostral-caudal gradient from the catheter tip (20,81,91), and the recent work of Wallace and Yaksh confirms this in a human study (170). In patients receiving IT morphine, CSF morphine concentrations decreased by distance from the catheter tip with a gradient that correlated with the infusion dose, and over a range of infusion rates of 0.1-1.0 mL/day.…”
Section: Csf Dynamicsmentioning
confidence: 74%
See 2 more Smart Citations
“…Many animal studies have shown a rostral-caudal gradient from the catheter tip (20,81,91), and the recent work of Wallace and Yaksh confirms this in a human study (170). In patients receiving IT morphine, CSF morphine concentrations decreased by distance from the catheter tip with a gradient that correlated with the infusion dose, and over a range of infusion rates of 0.1-1.0 mL/day.…”
Section: Csf Dynamicsmentioning
confidence: 74%
“…Many factors have been proposed and evaluated as contributing to differential drug distribution in the CSF. For instance, anatomic variation, postural changes, drug solution density, binding characteristics of drugs at the dorsal horn, CSF volume and variations in CSF pulsatile flow with heart rate, stroke volume, and respiratory cycle have been examined (20,156,170,281,283). Additionally, it has been suggested that the rate of dispersion in the CSF cannot be explained by diffusion alone (156,283).…”
Section: Intrathecal Infusion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Since North et al reported the first granuloma formation in 1991 , there have been many articles describing inflammatory mass lesions at the tips of intrathecal catheters, mostly in the form of case reports or case series . Intrathecal catheter tip granulomas have been reported to occur at a rate of 0.5–3% of cases, though these numbers are believed to be conservative estimates of the actual prevalence .…”
Section: Discussionmentioning
confidence: 99%